FREQUENCY OF HORMONE RECEPTORS AND HER-2/NEU RECEPTOR POSITIVITY IN DIFFERENT HISTOLOGY IN BREAST CANCER PATIENTS - Ravi, Ramchandani; Haider, Ghulam; Ahmed, Khalil; Zahoor, Saima; Sami, Abdus; Lata, Ramchandani (Journal of Ayub Medical College Abbottabad, 2020)
Background: This study was conducted to see the frequency of hormone receptors and Her-2/Neu positivity in different histology in breast cancer patients. Methods: It was a cross-sectional study conducted at the Department of Medical Oncology, Jinnah Postgraduate Medical Centre from June 2018- March 2019. Total 373 patients of age 22-81 years of which 360 female and 13 males, with histopathological proven diagnosis of breast cancer were included in the study using non-probability consecutive sampling technique. The immunohistochemistry (IHC) was performed on biopsy sample for the status of PR, ER and HER-2/Neu and the confirmation of Her-2/Neu was done by Fluorescent In situ Hybridization (FISH) technique if HER-2/Neu was equivocal by IHC testing. Information regarding demographics, family history, histology, grade, stage, metastatic site and other histopathological parameters were noted on predesigned proforma by the researcher. SPSS-23 was used to analyse data. Results: Total of 373 patients were included in the study. The mean patient age was 45.34±12.28 years. ER, PR, Her 2 Neu (IHC) & Her 2 Neu (FISH) were found positive in 206 (55.2%), 182 (48.8%), 121 (32.4%) & 23 (6.2%) patients, respectively. The histology with PR receptor & grade of tumour with ER & PR receptor showed statistical significance (p<0.05). Conclusion: ER, PR &HER-2/NEU expression in breast cancer vary among different population and it is very important to find out the frequency among different histopathological types as it is of predictive and prognostic value. So, it is recommended to look for these markers and treat them accordingly.